Women and Money: Unique Issues — Protecting Your Assets - Lynda Spence; Martie Gillen; Diann Douglas (EDIS)
Protecting your assets is similar to managing your risks. Managing risks means identifying and evaluating instances where you may experience a financial loss and then making a plan for how to deal with the situation. This publication shares some common ways you can protect your assets by purchasing different types of insurance, being aware of identity theft or fraud, and monitoring your credit reports. This 4-page fact sheet was written by Lynda Spence, Martie Gillen, and Diann Douglas, and published by the UF Department of Family Youth and Community Sciences, July 2013.